NEW FORMULAS FOR THE CRITICAL FORCES OF CYLINDRICAL SHELLS CALCULATION - Todchuk, Volodymyr (Proceedings of National Aviation University (archive), 2020)
Purpose: To show that within the framework of the linear theory, it was possible to obtain formulas for axial critical loads, the calculation results for which are in good agreement with experimental data. Method: An energetic solution method using the general linear theory of thin-walled shells. Results: New formulas for the critical loads of cylindrical shells are obtained. The analysis of the obtained results is carried out. Recommendations for their use are given. Discussion: Difficulties in theoretical determination of the critical loads of cylindrical shells under axial compression, which are close to the experimental data, forced researchers to seek empirical solutions. Many empirical relationships have been obtained that give different results and describe known experiments. However, there remains a need to theoretically find formulas that allow calculating the critical loads of cylindrical shells of any geometric parameters. Such formulas have been obtained. A comparison of the critical loads calculated using these formulas with empirical and experimental critical loads is carried out. The differences between them are minor.